Budidaya Tanaman Kubis Bunga (Brassica oleracea var. Botrytis L.) pada Berbagai Kombinasi Pupuk Kandang Kotoran Ayam dan EM4 - Hafizah, Nur; Adriani, Farida; Latifah, Jauhar (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
Cabbage cultivation in South Kalimantan has decreased productivity due to several factors including the lack of utilization of organic nutrients in cultivation techniques. The use of organic fertilizers such as chicken manure has an important role in improving soil quality and properties, including improving sandy soil structure. In addition to providing chicken manure as organic material, the addition of EM4 is also a bacterial fermentation of organic matter that fertilizes plants and nourishes the soil. This study aimed (i) to determine the response of growth and yield of cabbage to the combination of chicken manure and EM4, (ii) to obtain the best combination of chicken manure and EM4 concentration on the growth and yield of flower cabbage. This research was conducted in Tayur Village, North Amuntai District, Hulu Sungai Utara Regency, South Kalimantan Province from May to August 2021, using a single factor Randomized Block Design (RBD). The factors studied were e1 = chicken manure 25 tons/ha, e2 = chicken manure 25 tons/ha + 10 ml/l EM4, e3 = chicken manure 30 tons/ha + 15 ml/l EM4, e4 = chicken manure 35 tons/ha + 25 ml/l EM4. The observed variables were plant height, leaves, flowering age, harvest age, flower bud weight and flower bud circumference. The results of this study showed that the combination dose of chicken manure and EM4 concentration had a very significant effect on the variables of plant height at 28 DAP, had a significant effect. on the number of leaves aged 21 and 28 DAP, but had no effect on changes in plant height at 14 and 21 DAP, number of leaves at 14 DAP, age at flowering, harvesting age, crop weight and crop circumference.